Aplikasi Generalized Poisson Regression untuk Memodelkan Faktor yang Mempengaruhi Jumlah Kasus Baru Difteri di Provinsi Jawa Timur Tahun 2018 - Muhammad Jefri Badriawan; Soenarnatalina Melaniani (Media Gizi Kesmas, 2023)
Background: Diphtheria cases spread in almost all regions in Indonesia. In 2018 the highest number of diphtheria cases in East Java was 695 cases with a Case Fatality Rate (CFR) of 1.44%. Diphtheria is an acute infectious disease caused by Corynebacterium diphteriae bacteria. Environmental and behavior factors can be a cause of the spread of diphtheria. Objectives: The purpose of the study was to apply the Generalized Poisson regression to identify the factors that influence of diphtheria cases in 2018. Methods: The study used secondary data that had been published by the Provincial Health Office through data from the health profile of East Java Province in 2018. The population was a population in East Java Province in 2018 whose region consisted of 38 districts/cities. The sample in the study was diphtheria sufferers in East Java Province in 2018. The variable used in the study was the number of diphtheria cases as a dependent variable. The independent variable is the density of the population, the percentage of healthy homes, the percentage of households in a clean and healthy life behavior (CHLB), and the percentage of complete basic immunization. The data analysis used in the study is Generalized Poisson Regression Result: The results of the study get the best model of diphtheria case = Exp [2,995+ 0.01381 (CHLB household)]. Conclusion: The conclusion of the study is a significant variable affecting the diphtheria case in East Java Province in 2018 is a CHLB household.